PERANCANGAN PROTOTIPE LOW COST SMART HOME SYSTEM BERBASIS INTERNET of THINGS - Sarosa Castrena Abadi; Givy Devira Ramadani; Mindit Eriyadi (Politeknik Harapan Bersama Tegal, 2021)
Abstract The benefits of technology that can be applied to human problems nowadays one of them is in the process of control and monitoring of resources in a building in a close and in a long distance. The Internet of things are being continuously developed and implemented in all areas, that is because of the needs of devices that can be controlled and monitored remotely. In this study Smart Home System designed to be able to control all equipments in the home with any brand device, then the Smart Home System is able to monitor the state of the Home from the dangerous things such as smoke and gas with the addition of sensor devices that is needed by the user in a home and also with a low power consumption. The process of control and monitoring is done through web interface. The test results show the system can store the remote code for each TV and AC equipment and the code is reused by ESP8266 as a controller to remote all TV equipment and air conditioning with a different brands. In addition test results show the system can monitor and provide notifications through a Web view that can be accessed using a Web browser. Keywords: IOT , ESP8266, Smart , Home , low cost